Carbon Nanotube Driver Circuit for 6 × 6 Organic Light Emitting Diode Display - Zou, Jianping (2015)
Single-walled carbon nanotube (SWNT) is expected to be a very promising material for flexible and transparent driver circuits for active matrix organic light emitting diode (AM OLED) displays due to its high field-effect mobility, excellent current carrying capacity, optical transparency and mechanical flexibility. Although there have been several publications about SWNT driver circuits, none of them have shown static and dynamic images with the AM OLED displays. Here we report on the first successful chemical vapor deposition (CVD)-grown SWNT network thin film transistor (TFT) driver circuits for static and dynamic AM OLED displays with 6 × 6 pixels. The high device mobility of ~45 cm2V−1s−1 and the high channel current on/off ratio of ~105 of the SWNT-TFTs fully guarantee the control capability to the OLED pixels. Our results suggest that SWNT-TFTs are promising backplane building blocks for future OLED displays.